Optimization of PID Control for High Speed Line Tracking Robots - Balaji, V. (Elsevier B.V., 2015)
The paper focuses on the optimization of the classical PID control technique for implementation in a high speed line tracking robot. The control technique is tested on a prototype line tracking robot, which uses an array of ten Infra-Red reflective sensors to track a non-reflective line on a reflective surface. The paper describes in detail the various challenges that are specific to the mobile robot line tracking system and the adaptation of PID control to successfully control the highly non-linear and unstable system. Various forms of PID control are implemented and the merits and demerits of the same are discussed. A customized PID control implementation scheme is proposed which combines the aspects of closed loop PID control and open loop control. Â© 2015 The Authors.